Root Polytopes and Growth Series of Root Lattices - Ardila, Federico; Beck, Matthias; Hoşten, Serkan; Pfeifle, Julian; Seashore, Kim (SIAM journal on discrete mathematics, 2011)
The convex hull of the roots of a classical root lattice is called a root polytope. We determine explicit unimodular triangulations of the boundaries of the root polytopes associated to the root lattices An, Cn, and Dn, and we compute their f- and h-vectors. This leads us to recover formulae for the growth series of these root lattices, which were first conjectured by Conway, Mallows, and Sloane and Baake and Grimm and were proved by Conway and Sloane and Bacher, de la Harpe, and Venkov. We also prove the formula for the growth series of the root lattice Bn, which requires a modification of our technique. [PUBLICATION ABSTRACT]